Human Rights and Religion: A Sociological Perspective - Breskaja, Olʹga Jurʹevna (Journal for the scientific study of religion, 2018)
This essay aims to review mainstream literature and research perspectives on the sociology of human rights with the further focus on relationship between human rights and religion. We consider the challenges of late engagement of sociology with human rights and current narratives of the relationship of human rights and religion that encompass normativity as the central category of historically oriented sociology. We discuss the contribution of two empirical research mainstreams on human rights and religion and focus on a new field of study-sociology of religious freedom. A detailed new agenda for sociological research on human rights and religion is explored in the final part of our assessment.